STRATEGI PEMBELAJARAN DAN KEBIJAKAN SEKOLAH DALAM MENDUKUNG PENDIDIKAN INKLUSI UNTUK ANAK BERKEBUTUHAN KHUSUS (ABK) DI SEKOLAH DASAR - Salwa Dwi Tarishah; Noviatul Hikmah; Zulfa Dewina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Inclusive education for Children with Special Needs (ABK) is a challenge for teachers and schools. This research discusses learning strategies that teachers can apply in dealing with several types of ABK, namely dyslexia, slow learners, severe mental retardation, and specific learning disorders, as well as policies that need to be prepared by school principals to support inclusive education management. In the context of inclusive classes, teachers play an important role by implementing adaptive teaching methods, such as positive reinforcement, intensive mentoring, and adjustments to instructions and assignments. Meanwhile, supportive school principal policies, such as providing special facilities, teacher training, preparing an Individualized Education Plan (IEP), and collaborating with experts, are very necessary to create a friendly learning environment for ABK. This research recommends that teachers and schools work collaboratively to form strategies that are responsive to the individual needs of ABK, in order to increase the effectiveness of the learning process and encourage the achievement of the maximum potential of each child.